Comparative efficacy of inhaled corticosteroids and leukotriene modifiers depending on ASP299GLY-TLR-4 polymorphism in patients with bronchial asthma in the population of AR Crimea - Bisyuk Yu.A.; Kurchenko A.I.; Dubovyi A.I.; Kondratiuk V.E. (Medičnì Perspektivi)
The study included 39 patients with bronchial asthma. All patients at baseline were stratified into two groups with the genotype AA and AG of polymorphism Asp299Gly TLR-4. The study consisted of 2 periods: a 2-weeks’ run-in period when all patients received low-dose (125 mg) of fluticasone propionate once a day; 24-weeks’ treatment period when patients received fluticasone propionate once a day or 1 tablet (10 mg) of montelukast per day depending on randomization subgroups. The study results showed that taking of fluticasone propionate by patients with AA genotype TLR-4 for 24 weeks is more effective than montelukast taking; this is evi¬denced by a significant increase of FEV1 and improvement of indices of asthma control level (ACL) and quality of life of patients (AQLQ (S)). In patients with AG genotype clinical efficacy of montelukast is superior to fluticasone propionate.